Methods of Tooth Pulp Sampling for Isolation and Cultivation of Stem Cells - R. Ivančaková; T. Soukup; J. Suchánek; J. Karbanová (Czech Dental Chamber, 2006)
Mesenchymal stem cells (MSC) are capable of spontaneous generation of a whole spectrum of cells of mesenchymal origin. Moreover, they can converse even into elements of different embryonic stems. Such therapeutic potential may be expected only on human embryonic SC which, however, do not fulfill histocompatibility with the recipient tissues. Moreover, MSC may be isolated from relatively easily accessible source such as dental pulp, in contrast to such tissue specific SC as for example neural SC. When using the method of cultivation of SC isolated from human bone marrow we developed, SC were identified in the dental pulp tissue.Stem cells of dental pulp (SCDP) were isolated from extracted primary/permanent teeth with the application of enzyme dissociation protocol. The obtained cells were cultivated in the medium with 2% FBS and passaged three times weekly over 55 population divisions in all patients.Our results have shown that the isolated SCDP represent a homogeneous population of stem cells capable of self-renewal with similar characteristics as MSC of bone marrow.